PENGARUH KEBISINGAN TERHADAP KARYAWAN DI PLTD SENTRAL II PT. SEMEN PADANG - Deded Chandra (JURNAL GEOGRAFI, 2013)
Abstract This research aim to analyze the noise intensity in PLTD Sentral II PT Semen Padang. Analysing physiological trouble, psycological trouble, trouble of communication and hearing trouble from noise to employees in PLTD Sentral II PT Semen Padang. This research have the character of quantitative descriptive that is see the noise intensity and its influence to employees in PLTD Sentral II PT Semen Padang. For the data of noise intensity conducted by measurement use the appliance of sound level metre and while for the data of employees feeling noise influence conducted by giving kuisioner. Analyse the data use the analyse of univariat and bivariat. Result of measurement of noise intensity in PLTD Sentral II PT Semen Padang by using appliance of sound level metre at five visible measurement dot that its intensity have exceeded the value float the boundary specified for the workplace of by ministrial decree of labour No 51/Men/1999 that is 85 dB (A). physiological trouble of laboring employees in PLTD Sentral II PT Semen Padang the field got that experiencing of physiological trouble with the sigh at most happened that is headache. Psycological trouble of laboring employees in PLTD Sentral II PT Semen Padang the field got that experiencing of psychological trouble with the sigh at most happened that is concentration less in working caused by his is clunk. Laboring employees communications trouble in PLTD Sentral II PT Semen Padang got that experiencing of communications trouble with the friends work to scream. Laboring employees hearing trouble in PLTD Sentral II PT Semen Padang got by that experiencing of hearing trouble with the sigh which is at most happened by that is ear often felt to be stuffed up.